2014
DOI: 10.1088/0031-9155/59/24/7793
|View full text |Cite
|
Sign up to set email alerts
|

Online image guided tumour tracking with scanned proton beams: a comprehensive simulation study

Abstract: Tumour tracking with scanned particle beams potentially requires accurate 3D information on both tumour motion and related density variations. We have previously developed a model-based motion reconstruction method, which allows for the prediction of deformable motions from sparsely sampled surrogate motions tracked via an on-board imaging system (Zhang et al (2013 Phys. Med. Biol. 58 8621)). Here, we investigate the potential effectiveness of tumour tracking for scanned proton beam therapy using such an appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 44 publications
(58 reference statements)
0
64
0
Order By: Relevance
“…31,32,33 These effects, i.e., possible significant hot or cold spots within the treatment volume accumulated over the course of a single fraction, are shown to be mitigated by fractionation, 32 multiple rescanning, 33 and retracking. 34 In the case of MRPT, the real-time MR images at the rate of 4-8 frames per second may in fact be available to assist in the management of interplay effects. It may be possible to track in real-time a tumor margin and correspondingly alter or translate the pencil beam scanning pattern.…”
Section: B Mrpt Workflowmentioning
confidence: 99%
“…31,32,33 These effects, i.e., possible significant hot or cold spots within the treatment volume accumulated over the course of a single fraction, are shown to be mitigated by fractionation, 32 multiple rescanning, 33 and retracking. 34 In the case of MRPT, the real-time MR images at the rate of 4-8 frames per second may in fact be available to assist in the management of interplay effects. It may be possible to track in real-time a tumor margin and correspondingly alter or translate the pencil beam scanning pattern.…”
Section: B Mrpt Workflowmentioning
confidence: 99%
“…Using organ meshing methods to ensure geometric consistency between the selected CT and the MR extracted motion library, multiple 4DCT's can be generated for any patient using motion from this library, such as to model a wide variety of potential motions. Such data sets can then be used to test, a priori, the robustness of a plan, or a given motion mitigation approach, to a wide variety of motion scenarios . Indeed, by combining this approach with a surrogate driven motion model, it may even be possible, in principle at least, to generate a patient and breath‐cycle specific computational phantom on which to plan treatments.…”
Section: Knowledge Is Powermentioning
confidence: 99%
“…A dose simulation study for a tracked delivery with a scanned proton beam to a phantom geometry was performed by van de Water et al . A clinical simulation of online image guided tumor tracking with scanned proton beams was performed by Zhang et al . It was shown that interplay effects could be significantly reduced applying tracking.…”
Section: Motion Mitigationmentioning
confidence: 99%
“…Comparison of 4D dose distributions on an example slice using different motion mitigation strategies …”
Section: Motion Mitigationmentioning
confidence: 99%